Effect of enzymatic hydrolysis and nitrogen on Saccharomyces cerevisiae β-glucan production from Manihot utilissima and Maranta arunadinacea waste - Misri A Gozan; Fita Sefriana; Yemirta Yemirta; Muhammad Arif Darmawan (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2023)
This experiment utilised cassava (Manihot utillissima) and arrowroot (Maranta arunadinacea) wastes as the medium of propagation of Saccharomyces cerevisiae to produce β-glucan. The amyloglucosidase hydrolysed the waste, followed by fermentation in the nitrogenous medium by S. cerevisiae. The β-glucan pellet was extracted using 2% NaOH alkaline solution at 90°C for 5 hours, followed by a series of centrifugation processes. The highest glucose concentration from hydrolysis resulted from adding 57.5 mg amyloglucosidase enzyme for arrowroot waste with 95.93% conversion and 50 mg enzyme for cassava waste with 64.70% conversion. The highest amount was obtained for producing S. cerevisiae by adding 4.75 g peptone to all samples. The optimum number of cells was obtained at 1.61 x 108 colonies at t = 48 hours for arrowroot waste and 8.55 x 107 colonies at t = 48 hours for cassava waste. For β-glucan production, the highest number was obtained by using 3.99 g of peptone for cassava waste with a yield of 1.20% and by using 4.75 g of peptone for arrowroot waste with a yield of 1.23%. For β-glucan pellet, the highest number was 1.77 g L-1 (0.18 % b/v) from cassava waste medium and 1.91 g L-1 (0.19% b/v) from arrowroot waste. Mutant cells in the Yeast Extract–Peptone–Glycerol (YPG) medium produced 6.56 g L-1 (0.66% b/v) β-glucan pellet, while wild-type cells in the similar medium produced 1.84 g L-1 (0.18% b/v).